Influence of word of mouth communication towards indonesian online shopper purchase intention - Purwanegara, Mustika Sufiati; Yuliana, Eka (Jurnal Manajemen Teknologi, 2010)
Word-of-mouth (WOM) gives the consumer perceptions to engage in retail online shopping can include both utilitarian and hedonic shopping dimensions. To cater to these consumers, online retailers can create  a  cognitively  and  esthetically  rich  shopping  environment,  through  sophisticated  levels  of communication, as the personal influence, online community, and also by sharing they experienceSince the effect of word of mouth communications on marketing and has proven to stimulate online consumer's perceptions, 374 person of House of Taaj Facebookers in all over Indonesia, in which 280 female (75%) and 94 male (25%) has expressed their perceptions toward online purchase intention, and word of mouth. This research presumes that word of mouth from another online consumers, share information and features can influence online shopping intention and entice them to modify or even transform  their  original  shopping  predispositions  by  providing  them  with  attractive  and  enhanced interactive features and controls of buying. To achieve the research objectives and the test hypotheses, factor analysis, and linear regression are used to analyze the significant level of each variable indicator of this study. The result of the test may conclude that the Facebookers perceived more intention to search information by online, caused of the effectiveness of time using online community to search information  and review  the  other  experience.  A more  positive  online  shopping  experience  led  to consumers' positive perceptions for online purchase intention. Thus, this  study may  conclude that indicator variable of perception that really influence the Facebookers online purchase intentions are their perception towards the effectiveness of time that they can be used to evaluate, and find information by online, and the best indicator is their online community that can deliver and influence Facebookers online purchase intention.Keywords: Word Of Mouth, Perception, Purchase Intention, Online Purchase Intention